Does swimming at a moderate altitude favor a lower oxidative stress in an intensity-dependent manner? Role of nonenzymatic antioxidants - Casuso, R. A.; Aragon-Vela, J.; Lopez-Contreras, G.; Gomes, S. N.; Casals, C.; Barranco-Ruiz, Y.; Mercade, J. J.; Huertas, J. R. (High Altitude Medicine & Biology, 2017)
We aimed to describe oxidative damage and enzymatic and nonenzymatic antioxidant responses to swimming at different intensities in hypoxia.We recruited 12 highly experienced swimmers who have been involved in competitive swimming for at least 9 years. They performed a total of six swimming sessions carried out at low (LOW), moderate (MOD), or high (HIGH) intensity at low altitude (630 m) and at 2320m above sea level. Blood samples were collected before the session (Pre), after the cool down (Post), and after 15 minutes of recovery (Rec). Blood lactate (BL) and heart rate were recorded throughout the main part of the session. Average velocities did not change between hypoxia and normoxia.We found a higher BL in response toMOD intensity in hypoxia. Plasmatic hydroperoxide level decreased at all intensities when swimming in hypoxia. This effect coincided with a lower glutation peroxidase activity and a marked mobilization of the circulating levels of a-tocopherol and coenzyme Q10 in an intensity-dependentmanner.Our results suggest that, regardless of the intensity, no oxidative damage is found in response to hypoxic swimming in well-trained swimmers. Indeed, swimmers show a highly efficient antioxidant system by stimulating the mobilization of nonenzymatic antioxidants.